2012
DOI: 10.1111/j.1365-2559.2011.04116.x
|View full text |Cite
|
Sign up to set email alerts
|

Interactions and relationships of PTEN, ERG, SPINK1 and AR in castration‐resistant prostate cancer

Abstract: Te study supports the heterogeneous nature of CRPC and confirms a significant association between PTEN, ERG, AR and SPINK1. Characterizing combined markers will aid in defining PCA subgroups relevant to prognosis contributing to the design of improved therapeutic approaches for CRPC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
37
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 44 publications
7
37
1
Order By: Relevance
“…Moreover, SPINK1 overexpression has identified an aggressive subtype of ETS negative prostate cancer, validated in different cohorts (19). SPINK1 and ERG rearrangements have been found to be mutually exclusive in other studies as well (41,42), similar to our current findings. A study by Leinonen et al found SPINK1 overexpression to be present in 10% of prostate cancers and also found it to be associated with an aggressive form of the disease, although mutual exclusivity with ERG rearrangements were not observed in this particular study (43).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Moreover, SPINK1 overexpression has identified an aggressive subtype of ETS negative prostate cancer, validated in different cohorts (19). SPINK1 and ERG rearrangements have been found to be mutually exclusive in other studies as well (41,42), similar to our current findings. A study by Leinonen et al found SPINK1 overexpression to be present in 10% of prostate cancers and also found it to be associated with an aggressive form of the disease, although mutual exclusivity with ERG rearrangements were not observed in this particular study (43).…”
Section: Discussionsupporting
confidence: 93%
“…It has also been shown previously that prostate cancers with ERG rearrangement have a worse outcome under active surveillance(29), highlighting its potential importance in influencing therapeutic management. Furthermore, a study by Bismar et al suggests that molecular aberrancies in PTEN, ERG , and SPINK1 may be involved in the development of castration-resistant prostate cancer, emphasizing their clinical importance (42). Our current study highlights the significant differences that exist at the molecular level when prostate cancers from clinicopathologically similar AAM and CaM are compared.…”
Section: Discussionmentioning
confidence: 99%
“…Based on known function and interactions, these genes are grouped into non-random highly interconnected functional modules (Fig. 3), as most of the major biological pathways involved by these genes, including WNT, 32,33 VEGF, PTEN/PI3K/AKT/ mTOR, 24,34 and chemokine 35 signaling pathways, have previously been implicated in various stages of PCa progression and many have been found to interact with ERG and AR. Indeed, analysis of the individual signature genes suggest that ERG and AR combined expression leads to deregulation of multiple cellular processes including, cell cycle, cell growth and differentiation, transcriptional regulation, specific protein turnover as well as intra-and extra-cellular signaling ( Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…17 For example, it is known that AR, ERG, and PTEN genomic aberrations interplay in PCa and are responsible in part for the occurrence of CRPC. 24 For instance, PTEN loss has been associated with increased frequency of alterations in the PI3K signaling pathway. Furthermore, selective inhibition of either the PI3K or AR signaling pathways leads to activation of the other due to the relief of feedback inhibition, thereby giving rise to therapeutic resistance in treatments that target just one of these signaling pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Recent work has demonstrated that prostate tumors can be stratified by dominant genetic alterations, such as chromosomal rearrangements involving ETS family transcription factors [17]. In surgically resected Pca patients, Lippolis et al [18] and Bismar et al [19] confirmed exclusivity of SPINK1 overexpression and ETS gene fusions, but that is not the case in endocrine-treated patients [20]. In line with…”
Section: Expression and The Biological Role Of Spink1 In Prostate Cancermentioning
confidence: 89%